Vesical calculus on the end of forgotten DJ stent: a case report - Sharma, Ankur; Walia, Darshanjit Singh (International Journal of Research in Medical Sciences, 2017)
Double J stent provides a convenient way of draining upper urinary tract. However it is associated with many complications of which forgotten stent and associated comorbidity is an important factor. Careful monitoring of patients could exclude any possibility of a stent being forgotten at all. We present a case report of such complication of forgotten stent with formation of stone at the vesical end of DJ stent.